Interlanguage Interference of English and Russian Homonyms - Mamedova Madina Ashuraliyevna (Genius Journals, 2023)
This article discusses the interlingual interference of Russian and English homonyms. A comparative study of homonymy in English and Russian shows that, in general, lexical homonymy is manifested equally in both languages. The phenomenon of interlingual homonymy presents a significant difficulty in translating and learning a foreign language. At the same time, it does not lend itself to systematization and does not allow developing effective methods to overcome it. This gives particular importance to such a tool for describing and learning a language as a dictionary.
Keywords: interference; interlingual interference; intralingual interference; speech skills